Gender gaps in wages and non-monetary benefits: Evidence from Ethiopia's manufacturing sector - Tigabu Degu Getahun; Gebeyehu Manie Fetene; Heike Baumüller; Zaneta Kubik (University of Bonn, Center for Development Research (ZEF), 2024)
Using two rounds of panel firm- and worker-level data, this paper studies the gender gap in monetary and non-monetary compensation as well as work-related wellbeing among full-time workers in the agro-processing and leather sectors in Ethiopia. After controlling for year-fixed effects, the research reveals that women earn 35% less income from primary jobs and 40% less total income than men do. Some 40% of this primary job income gap and 43.3% of the income gap from all sources can be attributed to differences in human capital. Controlling for other worker, firm and manager characteristics as well as sector fixed effects do not meaningfully change the estimated coefficients. Child penalty explains part of the earning difference: the gender gap in total income between workers who do not have children is 11.7% while it is 37.6% among workers who have children. This difference is primarily because women who have children are 18.3% less likely to earn income from moonlighting and overtime work than men who have children do. Meanwhile, there is no statistically significant gender difference in moonlighting and overtime work among workers who do not have children. Gender earning differences are highest among medium skilled workers. Moreover, women are less likely to receive housing, discounted or complementary meals, or on-the-job training than men. Despite these discrepancies, women report to be happier and more satisfied, and are more likely to rate working conditions positively than men. This satisfaction and happiness may reduce their aspiration and quest for equal pay and non-monetary benefits. Narrowing human capital differences and providing aspiration building for women may help to reduce the gender earning gap.
Keywords: J16; J21; J28; J31; J33; J71; 330; Job quality; wellbeing; gender pay gap; inclusiveness; working conditions